2015
DOI: 10.1007/s10552-015-0610-8
|View full text |Cite
|
Sign up to set email alerts
|

Validation of clinical prognostic indices for diffuse large B-cell lymphoma in the National Cancer Data Base

Abstract: We validated the IPI and R-IPI as recorded by cancer registries to provide robust risk stratification in the general population with DLBCL, but a prognostic model using raw registry data provides superior performance. Explicit recording of prognostic factors is preferable to abstracting coarsened clinical indices for the purpose of population-based epidemiologic research. Considering low variation of survival explained by the standard clinical variables, incorporating molecular markers into registry data is ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
(57 reference statements)
0
12
1
1
Order By: Relevance
“…Five-year OS rates ranged from 86% in IPI ‘low-risk’ patients to 45% in IPI ‘high-risk’ patients. Our OS rates were higher than the 5-year OS rates reported for patients in a large validation study by Olszewski et al those authors reported 5-year OS of 74, 58, 49, and 33% for ‘low-risk’, ‘low-intermediate’, ‘high-intermediate’ and ‘high-risk’ patients, compared with 86, 67, 58, and 45%, respectively, in the present study ( 23 ). Five-year OS rates in our study were higher in all three R-IPI categories compared with the validation study (‘very good’ prognosis: 96% vs. 87%; ‘good’ prognosis: 73% vs. 64%; ‘poor’ prognosis: 51% vs. 41%, respectively), differences that may have been due to the characteristics of the two patient populations.…”
Section: Discussioncontrasting
confidence: 87%
“…Five-year OS rates ranged from 86% in IPI ‘low-risk’ patients to 45% in IPI ‘high-risk’ patients. Our OS rates were higher than the 5-year OS rates reported for patients in a large validation study by Olszewski et al those authors reported 5-year OS of 74, 58, 49, and 33% for ‘low-risk’, ‘low-intermediate’, ‘high-intermediate’ and ‘high-risk’ patients, compared with 86, 67, 58, and 45%, respectively, in the present study ( 23 ). Five-year OS rates in our study were higher in all three R-IPI categories compared with the validation study (‘very good’ prognosis: 96% vs. 87%; ‘good’ prognosis: 73% vs. 64%; ‘poor’ prognosis: 51% vs. 41%, respectively), differences that may have been due to the characteristics of the two patient populations.…”
Section: Discussioncontrasting
confidence: 87%
“…Such a model, incorporating disease-specific risk factors, as well as sociodemographic indicators of general mortality, has been shown in DLBCL and PTCL to provide a better stratification of OS using cancer registry data than the IPI. (Olszewski et al, 2015; Petrich et al, 2015) Model sensitivity to the proportional hazard assumption was evaluated by plotting smoothed scaled Schoenfeld residuals versus time. All estimates are presented with 95% confidence intervals (95%CI).…”
Section: Methodsmentioning
confidence: 99%
“…Prognosis in DLBCL has been historically assessed using clinical features comprising the International Prognostic Index (IPI), but in the era of rituximab-based immunochemotherapy the IPI explains less than 25% of variation in overall survival (OS) and poorly separates the highest-risk subgroups [9, 12]. The enhanced IPI (which improved on the specification of age and lactate dehydrogenase [LDH] as non-binary variables) has identified involvement of CNS, liver/gastrointestinal (GI) tract, lung, or marrow as additional unfavorable prognostic factors [9].…”
Section: Assessment Of Prognosis In Dlbclmentioning
confidence: 99%